The prevalence of developmental coordination disorder in children: a systematic review and meta-analysis - Li, Huaqiang; Ke, Xiaohua; Huang, Dunbing; Xu, Xiaqing; Tian, Huan; Gao, Jiaxin; Jiang, Cai; Song, Wei (Frontiers in Pediatrics, 2024)
Purpose Synthesize previous evidence and clarify the prevalence of developmental coordination disorder (DCD) in children by Meta-analysis.Methods A comprehensive computerized search of databases, including PubMed, Embase, Web of Science, The Cochrane Library, CHINAL, and PsycINFO databases was conducted to identify relevant national and international publications on DCD prevalence in children up to December 18, 2023. The meta-analysis of prevalence was conducted using Stata 18.0.Results A total of 18 papers involving 31,203 patients were included. The prevalence of children with DCD was found to be 5%. Subgroup analysis showed that prevalence was 7% (95% CI 4% -10%) and 4% (95% CI 3% -7%) for boys and girls, respectively; 4% (95% CI 2% -8%), 2% (95% CI 2% -2%), and 6% (95% CI 3% -10%) in Asia, Europe, and North America, respectively, and 18% (95% CI 8% -31%) and 6% (95% CI 4% -7%) for preterm(＜37W) and term infants(≥ 37W), respectively. The prevalence of very low birth weight children(＜1250g) with DCD was found to be 31%.In this study, we found that the prevalence of children with DCD in the general population was 5% and that preterm infants (<37W) and very low birth weight infants (<1250g) have a higher prevalence of DCD and require early screening and regular follow-up.